AI system support for conceptual design proceedings of the 1995 Lancaster International Workshop on Engineering Design, 27-29 March 1995 - Sharpe, John (John E. E.) (Springer, 1996)
It is well-known that some 85% of the resources necessary to design and bring to market a product are committed by decisions taken in the first 10% of the design activity. This together with the wish to reduce further the time-to-market of high quality innovative products has increased the need for computer support at the conceptual design stage of the engineering design process life-style. This proceedings firmly focuses on the continuing research into new uses of Artificial Intelligence (AI) during the conceptual design process. It shows how novel applications of AI may be integrated with aspects of solid modelling, simulation optimisation and multiple criterion decision- making. A particular emphasis is placed on the use of AI methods in the overall design of products from major Civil Engineering structures to Consumer Electronics.